MIFOLOGIYALÍQ OBRAZLARDÍŃ IZERTLENIWI - Kabilova, G.B. (SCIENCE and SOCIETY, 2024)
The article is devoted to the study of mythological images that gained significance in the emergence and development of folklore, and today perform an artistic function in folklore genres. Information is given on how the myth was scientifically and theoretically studied by foreign scientists, and research was also carried out in this direction among the Turkic peoples. Scientific and theoretical views and opinions regarding the function and history of the study of mythological images found in Karakalpak folk tales which are considered one of the genres of folklore, are presented. Theoretical discussions about mythological images with the opinions of scientists of the Turkic peoples are given, and these images were confirmed by personal scientific opinions. The final scientific and theoretical opinions are expressed on the topical issue of studying the artistic function of mythological images in the plot of Karakalpak folk tales and the classification of mythological images.
Keywords: myth; mythology; folklore; image; fairy tale